2022
DOI: 10.3389/fpubh.2022.919347
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Spicy Food Intake and Risk of Hyperuricemia Among Chinese Adults

Abstract: Hyperuricemia is associated with substantial health and economic burden all over the world. Dietary habits are an important influencing factor of hyperuricemia. This study aimed to investigate the relationship between spicy food intake and hyperuricemia based on a large population. A total of 22,125 individuals aged 30–79 were enrolled in China Multi-Ethnic Cohort (CMEC), Chongqing region. Spicy food intake information was collected by a standardized questionnaire. The association between spicy food intake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Compared with people who never consumed spicy food, those who ate them frequently were more likely in younger man group. 57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with people who never consumed spicy food, those who ate them frequently were more likely in younger man group. 57 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with people who never consumed spicy food, those who ate them frequently were more likely in younger man group. 57 Psychotropic medications can affect biochemical markers of patients, such as SUA, BMI, and TG(Triglyceride). 58,59 The most explicit thing was the use of antipsychotics, especially atypical antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…This area was famous for hot pot and had a very high rate of alcohol consumption every day, so the sample could be representative. Second, our research had a large sample of individuals and we adjusted for many confounding factors in a large range 42. This epidemiological study provided some explorations and thoughts about the relationship between drinking alcohol and HUA.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our research had a large sample of individuals and we adjusted for many confounding factors in a large range. 42 This epidemiological study provided some explorations and thoughts about the relationship between drinking alcohol and HUA. Lastly, the determination of HUA required not only the patient’s self-reported diagnosis, but also the laboratory testing about individuals’ blood and uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that consuming spicy food had a beneficial influence on total and specific mortality [ 7 , 8 ], lipid profiles [ 9 , 10 ], as well as cancer [ 11 – 13 ]. While others suggested that spicy food consumption may have adverse or no effect on diseases such as dyslipidemia [ 14 , 15 ], diabetes mellitus [ 16 ], obesity [ 17 19 ], hyperuricemia [ 20 , 21 ], and cancer [ 22 ]. Regarding the association between spicy food and hypertension, results from previous studies are also conflicting.…”
Section: Introductionmentioning
confidence: 99%